Special Issue “Viral Shedding and Transmission in Zoonotic Diseases” - Kateri Bertran; Martí Cortey; Miriã F. Criado (Viruses, 2022)
The papers published in this Special Issue represent only a glimpse of the vast diversity of viral infectious diseases, and the complexity of their interactions with the host, that have an impact on human and animal health [...]